2017
DOI: 10.1002/jcb.26489
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐137 inhibited inflammatory response and apoptosis after spinal cord injury via targeting of MK2

Abstract: Spinal cord injuries are common and troublesome disorder, which is mediated by various signal pathways and mechanisms. MK2 is also involved in numerous inflammatory diseases including spinal cord injury. The role of microRNA-137 (miR-137) and its detailed working mechanism in spinal cord injuries remain unclear. In the present study, we found that an elevated MK2 but a decreased miR-137 was expressed in serum specimens of patients with spinal cord injury and in hydrogen peroxide-treated C8-D1A and C8-B4 cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 49 publications
(52 reference statements)
2
27
0
Order By: Relevance
“…SCI is a serious CNS injury and can result in permanent movement disorders, cognition impairment and even paralysis [26]. Although it has been widely discovered that the mechanisms underlying the secondary injury of SCI involve numerous molecular and biochemical changes such as inflammatory activation, production of free radicals, axonal plasticity and neuronal cell death [27], SCI still remains one of the major challenges in clinical practice [28].…”
Section: Discussionmentioning
confidence: 99%
“…SCI is a serious CNS injury and can result in permanent movement disorders, cognition impairment and even paralysis [26]. Although it has been widely discovered that the mechanisms underlying the secondary injury of SCI involve numerous molecular and biochemical changes such as inflammatory activation, production of free radicals, axonal plasticity and neuronal cell death [27], SCI still remains one of the major challenges in clinical practice [28].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-544a level was significantly reduced after SCI and its high expression level alleviated the inflammation and took part in the recovery of SCI (Yang et al, 2018). Moreover, previous studies revealed that miR-137 could show the suppressive effect on the inflammatory response and apoptosis after SCI (Gao et al, 2018). Importantly, it is interesting that miR-362-3p could be regulated after SCI, which demonstrated by previous research (Zhu et al, 2017).…”
Section: Discussionmentioning
confidence: 67%
“…Considering the vital functions of miR-137-3p 19,20,22,26 and Neu-roD1 (ref. 14, 27 and 28) in the nervous system, we investigated their role in the SCI cell model.…”
Section: Curcumin Alleviates Lps-mediated Regulation On Mir-137-3p Anmentioning
confidence: 99%
“…15,16 The imbalance of miRNA is related to a variety of central nervous system diseases, and additionally, it is also associated with glial differentiation. 17,18 miRNA (miR)-137-3p, a welldocumented tumor repressor, has been reported to function in SCI mice/rat models 19,20 induced by spinal cord contusion, as well as in SCI cell models induced by high glucose and H 2 O 2 . 21,22 Besides, the down-regulation of miR-137-3p is invariably observed in the serum from SCI patients, rat SCI models, and H 2 O 2 -induced astrocytes in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation